2000
DOI: 10.1002/(sici)1097-4679(200004)56:4<449::aid-jclp1>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Global assessment of functioning (GAF) ratings: Determinants and role as predictors of one-year treatment outcomes

Abstract: Objective: To assess the adequacy of global ratings of patients' psychosocial functioning, which are an integral part of the current system for obtaining multidimensional psychiatric diagnoses and are embodied by the Global Assessment of Functioning (GAF) Scale as AXIS V of the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (American Psychiatric Association, 1994). Method: We identified a sample of 1,688 patients with substance use disorders, many of whom also had psychiatric disorders; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
81
1
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(89 citation statements)
references
References 43 publications
5
81
1
2
Order By: Relevance
“…To date, findings as to the usefulness of clinician ratings in predicting psychiatric outcome have been mixed. Our results are consistent with those who have found little association between clinical ratings and rehospitalization (Moos et al, 2000;Parker et al, 2002), employment (Moos, Nichol, & Moos, 2002), and bed days (Parker et al, 2002). However, some studies have reported an association between clinical judgment and hospitalization (Hendryx et al, 2003;Monnelly, 1997;Vetter & Koller, 1996;Walker et al, 1996), service costs (Ruggeri, Biggeri, Rucci, & Tansella, 1998), and employment (Vetter & Koller, 1996).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…To date, findings as to the usefulness of clinician ratings in predicting psychiatric outcome have been mixed. Our results are consistent with those who have found little association between clinical ratings and rehospitalization (Moos et al, 2000;Parker et al, 2002), employment (Moos, Nichol, & Moos, 2002), and bed days (Parker et al, 2002). However, some studies have reported an association between clinical judgment and hospitalization (Hendryx et al, 2003;Monnelly, 1997;Vetter & Koller, 1996;Walker et al, 1996), service costs (Ruggeri, Biggeri, Rucci, & Tansella, 1998), and employment (Vetter & Koller, 1996).…”
Section: Discussionsupporting
confidence: 92%
“…At hospital admission, when the clinician may be unfamiliar with the patient and the patient is in acute distress, the clinician may not be able to assess accurately the full extent of his or her social and occupational functioning. Previous research suggests GAF scores at hospital admission are minimally related to indicators of social and occupational functioning (Moos et al, 2000;Parker et al, 2002). Level of social and occupational functioning prior to hospital admission is, however, related to readmission (Oiesvold et al, 2000;Russo et al, 1997b).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The GAF is based on clinician report, and ranges from 0 (very low functioning across domains) to 100 (superior functioning in a wide range of activities), with higher scores indicative of better functioning. The GAF has been shown to be a reliable correlate of psychiatric symptoms, clinical diagnoses, and various other clinical outcomes (Friis et al 1993;Moos et al 2000). Additionally, the GAF has displayed reliability and concurrent validity in the current study's setting (Reardon et al 2002).…”
Section: Global Assessment Of Functioningmentioning
confidence: 60%